[Fe19] "Super‐Lindqvist" Aggregate and Large 3D Interpenetrating Coordination Polymer from Solvothermal Reactions of [Fe2(OtBu)6] with Ethanol1. Issue 35 (15th July 2015) - Nachtigall, Olaf; Kusserow, Matthias; Clérac, Rodolphe; Wernsdorfer, Wolfgang; Menzel, Michael; Renz, Franz; Mrozinski, Jerzy; Spandl, Johann
Abstract The syntheses, crystal structures, and physical properties of [HFe19O14(OEt)30] and Fe11(OEt)24∞ are reported. [HFe19O14(OEt)30] has an octahedral shape. Its core with a central Fe metal ion surrounded by six μ6‐oxo ligands is arranged in the rock salt structure. Fe11(OEt)24∞ is a mixed‐valence coordination polymer in which FeIII metal ions form three 3D interpenetrating (10, 3)‐b nets. The arrangement of the FeIII ions can also be compared to that of Si ions in α‐ThSi2. Thus, the described structures are at the interface between molecular and solid‐state chemistry.